Cretan Bronze Age Pithoi : traditions and trends in the production and consumption of storage containers in Bronze Age Crete - Chrēstakēs, Kōstantinos S. (Prehistory monographs, 2005)
Ch. 1.A formal typology for pithoi --Ch. 2.Decorative patterns and style --Ch. 3.The use of pithoi --Ch. 4.Traditions and trends in the production and consumption of pithoi.